Pengaruh Adopsi Cloud Accounting, Literasi Digital Keuangan dan Kesiapan Infrastruktur TI terhadap Kualitas Pelaporan Keuangan UMKM - Annisah Febriana; Ratih Dewi Titisari Haryana; Teguh Setiawan Wibowo (LPPM STIE YAPAN, 2025)
Accounting digitization is an important need for MSMEs because the quality of financial reporting determines access to financing, business control, and managerial decision-making. This study aims to analyze the influence of cloud accounting adoption, financial digital literacy, and information technology infrastructure readiness on the quality of MSME financial reporting. The study uses a quantitative approach with a survey method on 120 MSME actors in the trade and service sector in Surabaya who have recorded transactions digitally. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression. The instrument test results show that all items are valid and reliable. The regression results prove that the adoption of cloud accounting has a positive and significant effect on the quality of financial reporting. Financial digital literacy and the readiness of information technology infrastructure also have a positive and significant effect. Simultaneously, the three variables had a significant effect with the Adjusted R Square of 0.593. These findings show that the quality of MSME financial statements is not only determined by the use of applications, but also by the ability of users and the readiness of supporting technology. The implications of the research emphasize the importance of digital accounting training, assistance in the use of applications, and strengthening the digital infrastructure of MSMEs.